2007
DOI: 10.1177/0146167207309194
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Implicit and Explicit Measures of Attitudes and Measures of Behavior: Evidence of Moderation by Individual Difference Variables

Abstract: The moderating role of individual difference variables (Self-Reported Habit Index [SRHI], Need for Cognition [NFC]) on relationships between implicit (Implicit Association Test [IAT], Extrinsic Affective Simon Test [EAST]) or explicit measures of attitude and behavior is assessed in two studies. A dissociation pattern is found on self-report diary measures of behavior. In Study 1, the EAST-behavior relationship is moderated by SRHI; explicit measures of the attitude-behavior relationship are moderated by NFC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
92
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 42 publications
8
92
0
4
Order By: Relevance
“…Moderation of training effects by inhibitory self-control 17 As predicted, implicit evaluation training affected snack intake only for participants low higher inhibitory self-control would be expected to be able to inhibit unwanted impulses and 14 act in a manner consistent with personal goals (e.g., limit unhealthy snack intake despite …”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Moderation of training effects by inhibitory self-control 17 As predicted, implicit evaluation training affected snack intake only for participants low higher inhibitory self-control would be expected to be able to inhibit unwanted impulses and 14 act in a manner consistent with personal goals (e.g., limit unhealthy snack intake despite …”
mentioning
confidence: 79%
“…For positive implicit attitudes towards candy were more strongly related to subsequent candy 15 intake than for individuals with higher inhibitory control. Similarly, Nederkoorn, Houben, 16 Hofmann, Roefs, and Jansen (2010) found that only among participants with lower inhibitory 17 control did an implicit preference for snack food predict higher weight gain over one year. 18 Likewise, in the alcohol domain, more positive alcohol evaluations predicted higher levels of 19 alcohol use and alcohol problems, but again, only among those with low inhibitory control 20 ).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Implicit evaluations of unhealthy food and the weight-management goal-concept have previously been found to be related to indices of unhealthy eating behaviour, including self-reported and lab-based measures of food intake, self-reported resistance of unhealthy food temptations, weight gain, and BMI (Ayres et al, 2010;Conner et al, 2007;Dube, 2007;Friese et al, 2008;Hofmann et al, 2008;Perugini, 2005;Prestwich et al, 2011;Richetin et al, 2007). The current study contributed to an understanding of the relationship between these implicit evaluations and both the experienced temptation to consume, and the consumption of unhealthy snack food in a sample of young women motivated to manage weight through healthy eating.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, individuals' implicit evaluations of a stimulus (i.e., the extent to which the stimulus is associated with positive affect) have been found to predict the tendency to approach that stimulus across time and situations (e.g., Chen & Bargh, 1999;Dovidio, Kawakami, Johnson, Johnson, & Howard, 1997;Duckworth, Bargh, Garcia, & Chaiken, 2002;Ferguson & Bargh, 2008). In the area of healthy eating, research has shown a correlation between a more positive implicit evaluation of unhealthy food and lab-based choice and actual purchase of unhealthy over healthy food items, higher intake of unhealthy snack food in lab-based tasks or self-report snack diaries, higher levels of weight gain, and higher BMI (Ayres, Prestwich, Conner, & Smith, 2010;Conner, Perugini, O'Gorman, Ayres, & Prestwich, 2007;Dube, 2007;Friese, Hofmann, & Wanke, 2008;Hofmann, Gschwendner, Friese, Wiers, & Schmitt, 2008;Perugini, 2005;Prestwich, Hurling, & Baker, 2011;Richetin, Perugini, Prestwich, & O'Gorman, 2007). However, not all studies have found this relationship (Czyzewska & Graham, 2008;Karpinski & Hilton, 2001;McKenna, 2010;Nederkoorn, Houben, Hofmann, Roefs, & Jansen, 2010).…”
mentioning
confidence: 99%